Folksonomies de la qualité de l’air - Florian Charvolin (Revue d'anthropologie des connaissances)
The paper accounts for a classification experiment of ambient air particles measurement’s sessions by people to whom was lent a microsensor, in the “checkbox” project organized by sociologists and experts of a certified association of air quality surveillance (Aasqa). It focuses on the diversity of these labels - or folksonomies - posted on the database along with data, by 70 people, whether they follow a standard codification rule or invent them along the way. The sociologists of Checkbox are able to underline the successful compromise achieved between lay metrological imagination and expertise normalizing air quality monitoring.